(untitled) (Global Journal of Science Frontier Research, 2014)
The aqueous extracts of three edible mushroom species viz. Agaricus bisporus, Calocybe indica and Pleurotus ostreatus were analyzed for antioxidant activity using in vitro biochemical assays. In this study, the effect of widely used three cooking conditions, boiling, steaming and microwaving on the antioxidant content of the mushroom species were explored by comparatively analyzing the raw and cooked mushrooms. Cooking the food affects the total antioxidant content due to release of antioxidant, destruction or creation of redox-active metabolites. The radical scavenging ability and reducing power were observed to increase in cooked mushrooms while the ion chelating ability decreased than the fresh one. The DPPH radical scavenging ability for fresh P.ostreatus, A.bisporus and C.indica were 44.7, 42.7 and 40.3% respectively at the highest concentration. The scavenging ability for steam cooked P.ostreatus, A.bisporus and C.indica were 94.4, 91.8 and 89.3% respectively. The overall results suggest that the total antioxidant activity of the mushroom species were in the order of P.ostreatus> A.bisporus >C.indica. Among the cooking methods adopted in this study, the antioxidant content was highest in steam cooked mushrooms followed by boiled and microwaved. Thus, steaming is considered as the best cooking method of choice in order to release/ conserve antioxidants in mushrooms.